Effects of Substrate to Inoculum Ratio on the Biochemical Methane Potential of Piggery Slaughterhouse Wastes - Yoon, Young-Man (Asian-Australasian Association of Animal Production Societies (AAAP) and Korean Society of Animal Science and Technology (KSAST), 2014)
The aim of this study was to assess the effect of substrate to inoculum ratio (S/I ratio) on the biochemical methane potential (BMP) and anaerobic biodegradability (D(deg)) of different piggery slaughterhouse wastes, such as piggery blood, intestine residue, and digestive tract content. These wastes were sampled from a piggery slaughterhouse located in Kimje, South Korea. Cumulative methane production curves for the wastes were obtained from the anaerobic batch fermentation having different S/I ratios of 0.1, 0.5, 1.0, and 1.5. BMP and anaerobic biodegradabilities (D(deg)) of the wastes were calculated from cumulative methane production data for the tested conditions. At the lowest S/I ration of 0.1, BMPs of piggery blood, intestine residue, and digestive tract content were determined to be 0.799, 0.848, and 1.076 Nm(3) kg(−1)-VS(added), respectively, which were above the theoretical methane potentials of 0.539, 0.644, and 0.517 Nm(3) kg(−1)-VS(added) for blood, intestine residue, and digestive tract content, respectively. However, BMPs obtained from the higher S/I ratios of 0.5, 1.0, and 1.5 were within the theoretical range for all three types of waste and were not significantly different for the different S/I ratios tested. Anaerobic biodegradabilities calculated from BMP data showed a similar tendency. These results imply that, for BMP assay in an anaerobic reactor, the S/I ratio of anaerobic reactor should be above 0.1 and the inoculum should be sufficiently stabilized to avoid further degradation during the assay.